Comparison Between Two NSAIDs (Non selective & selective COX-2 Inhibitor) According to their Renal Toxicity on Elderly People - Hadi, Haydar F. (Al Mustansiriyah Journal of Pharmaceutical Sciences, 2007)
The nonsteroidal anti-inflammatory drugs (NSAIDs) are widly used all over the world for different rheumatic musculoskeletal disorders. Like any other chemical compounds, they have different side effects like renal toxicity that becomes very serious when used for long time especially from elderly people whose already have a reduced renal function or those This with renal or cardiac problems that may increase the incidence of such toxicity. study focusing on this point, by comparing between 2 NSAIDs, a non selective-COX inhibitor (Indomethacin) and selective COX-2 inhibitor (Meloxicam) according to their renal toxicity on elderly patients, depending on changes in values of blood urea nitrogen (BUN), serum creatinine (S. Cr.) & serum potassium (S. K+) concentrations as parameters of such toxicity. In another way we investigate whether the renal or cardiac problems will increase such toxicity of NSAIDs on elderly patients or not. The study involved 80 elderly patients, healthy and with renal or cardiac problems, selected from rheumatologic outpatient clinic and given one of the 2 NSAIDs as adrug of choice for their present complaints for a period of 15 days. It was clearly appeared from results, that both NSAIDs couse similar extent of renal side effects and the presence of renal and/or cardiac problems could increase the susceptibility of such toxicity especially renal impairment & renal hypertension.